Od filozofije poučevanja do poučevanja filozofije: Festschrift Rudi Kotnik (University of Maribor Press, 2025)
From Philosophy of Teaching to Teaching Philosophy: Festschrift Rudi Kotnik. This scientific monograph is dedicated to Rudi Kotnik, retired associate professor of philosophy at the University of Maribor. It begins with a contribution by the honoree himself, which serves as motivation for the other contributions. The monograph is divided into three sections, reflecting his pedagogical and research enthusiasm for exploring the ’Why, What, and How’ questions of the purpose of teaching and learning philosophy in a comprehensive and socially responsible manner. In the first section, the authors deal with the reasons, purpose, and justification for teaching and learning philosophy. They emphasize the transformative power of philosophy, which goes beyond critical thinking, as it leads to changes in education, the individual/self, and the world. Philosophy should cultivate cognitive virtues (such as courage, curiosity, and open-mindedness) and promote pluralism and cosmopolitanism. The second section explores answers to the questions of what teaching and learning philosophy is and what to teach and learn, specifically by focusing on the very definition and content of teaching and learning philosophy. In the third and final set of discussions, the authors address the question of how to teach philosophy. The common ground is the elements of methods based on cooperation, mutual respect, and dialogue. They emphasize that teaching and learning philosophy are also ways of doing philosophy.